Pengaruh Disiplin, Keselamatan dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan CV. Heaven Sentosa - Muhammad Iqbal Syahputra; Anton Budi Santoso (Universitas Batanghari, 2023)
The purpose of this research is to know how job discipline, health and safety work affects employees' performance on CV. Heaven Sentosa. For the method used in the study is by using a quantitative method using the survey method through the questionnaires handed out to employees. Especially those on CV. Heaven Sentosa by involving 31 employees. The data analysis techniques used in this study are valiance and reliability tests, descriptive analysis, classic assumptions test, linear regression tests, and hypothetical tests. Data analysis is done with the help of the SPSS 25 (Stastistic Product And Service Solution) application program. Research shows that discipline (x rays) and occupational safety and health (k3) (x files) have significantly and positively affected the performance of employees (y) CV. Heaven Sentosa. This suggests that the higher the level of employee discipline in the work, as well as the more secure and comfortable workers feel during the work, the better the performance by employees can be.